Preparation, characterization and photoluminescence of nanocrystalline calcium molybdate - Anukorn Phuruangrat (2018)
Nanocrystalline calcium molybdate was successfully synthesized from Ca(NO 3) 2 and Na 2MoO 4 in ethylene glycol using a microwave radiation method. Body-centered tetragonal structured calcium molybdate with narrow nanosized distribution was detected using XRD, SAED and TEM. A diffraction pattern was also simulated and was found to be in accordance with those obtained from the experiment and JCPDS standard. Raman and FTIR spectra show the Mo-O prominent stretching bands in the [MoO 4] 2- tetrahedrons at 879.59 and 743-895 cm -1, respectively. Photoluminescence emission of CaMoO 4 was detected at 477 nm, caused by the annihilation of a self-trapped excitons from the [MoO 4] 2- excited complex. © 2009 Elsevier B.V. All rights reserved.